2017
DOI: 10.1007/s12105-017-0867-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological and Immunohistochemical Study of Head and Neck Langerhans Cell Histiocytosis from Latin America

Abstract: Langerhans cell histiocytosis (LCH) is an inflammatory myeloid neoplastic proliferation with variable clinical behavior caused by the accumulation of CD1a/CD207 histiocytes, associated with a variable number of eosinophils, lymphocytes, plasma cells and multinucleated giant cells, most commonly observed in male children. LCH is uncommon in the head and neck region, occurring as ulcerated and reddened plaques or nodules that cause destruction of adjacent soft tissues and bone. The exact etiology of LCH is still… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 46 publications
0
22
0
6
Order By: Relevance
“…Step 1 consisted of a collaborative study and Step 2 consisted of a review of the literature of single cases or case series of CEOT published across five electronic databases. The present 2‐step study was structured in accordance with studies reported elsewhere (Bedran et al., ; de Arruda et al., ; Vasconcelos et al., ).…”
Section: Methodsmentioning
confidence: 86%
“…Step 1 consisted of a collaborative study and Step 2 consisted of a review of the literature of single cases or case series of CEOT published across five electronic databases. The present 2‐step study was structured in accordance with studies reported elsewhere (Bedran et al., ; de Arruda et al., ; Vasconcelos et al., ).…”
Section: Methodsmentioning
confidence: 86%
“…Langerhans cell histiocytosis is an uncommon disorder with an indefinite pathogenesis and a wide range of clinical manifestations . Recently, BRAF V600E mutations which participate in uncontrolled cell division have been identified in half of LCH patients leading us to consider this disease as a neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…The most affected oral soft tissues by LCH are the gingiva and the hard palate. Oral changes may be the only or the initial manifestation of the disease . Head and neck involvement includes cervical lymphadenopathy, mastoiditis, and otitis media that often present with multifocal involvement…”
Section: Discussionmentioning
confidence: 99%
“…Apesar de haver vários estudos avaliando a infiltração de células imunes na HCL, eles não permitem fazer uma análise comparativa entre os diversos subgrupos de células inflamatórias ou até mesmo uma análise comparativa da HCL afetando adultos e crianças. Assim, dentro destes estudos, podemos citar aqueles avaliando células CD3+ (Senechal et al, 2007;Nagarjun et al, 2008;Quispel et al, 2015;Bedran et al, 2017), células CD4+ (Nagarjun et al, 2008), células CD8+ (Nagarjun et al, 2008Alexandrescu et al, 2012), células CD15+ (Nagarjun et al, 2008, células CD20+ (Senechal et al, 2007;Nagarjun et al, 2008;Bedran et al, 2017), células CD25+ (Quispel et al, 2015), células CD56+ (Nagarjun et al, 2008, células TIA-1+ (Nagarjun et al, 2008), células CD68+ (Nagarjun et al, 2008Alexandrescu et al, 2012), células Mac387+ (Nagarjun et al, 2008, células CD204+ (Ohnishi et al, 2010), células FOXP3+ (Senechal et al, 2007;Alexandrescu et al, 2012;Quispel et al, 2015;Zeng et al, 2016), células Th17+ (Coury et al, 2008) e mastócitos (Nagarjun et al, 2008). Notavelmente, apesar disso, apenas poucos estudos examinaram o significado patológico de macrófagos polarizados (Ohnishi et al, 2010) e LTregs (Senechal et al, 2007) na HCL, porém com metodologia diferente da que se pretende desenvolver no presente projeto de pesquisa.…”
Section: Introductionunclassified
“…Além disso, escassos LCs em torno das células lesionais da HCL foram observados, através dos marcadores CD56 (média, 4,0), CD57 (média, 2,9), granB (média, 1,7) e Perf (média, 0,6) (Tabela 4), sendo estes dois últimos indicadores de expressão de grânulos citotóxicos (Figura 5). (Senechal et al, 2007;Nagarjun et al, 2008;Coury et al, 2008;Ohnishi et al, 2010;Alexandrescu et al, 2012;Quispel et al, 2015;Zeng et al, 2016;Bedran et al, 2017). Além disso, há outros estudos avaliando os marcadores PDL1, CD14, CD40, CD68, CD80, CD86 e CD208, porém somente enfatizando a expressão dos mesmos em células lesionais na HCL (Tazi et al, 1999;Geissmann et al, 2001;Laman et al, 2003;Senechal et al, 2007;Sahm et al, 2012;Zeng et al, 2016).…”
Section: Introductionunclassified